Pengaruh Pergantian Auditor, Kesulitan Keuangan, dan Reputasi Kap Terhadap Audit Delay pada Perusahaan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2022 - Sekar Puspita; Dwi Saraswati (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study was to determine the effect ofauditor changes, financial difficulties, and KAP reputation onaudit delay in real estate and real estate companies listed onthe Indonesia Stock Exchange in 2019 - 2022. Industrial development in Indonesia is increasing. This can be seen fromthe increasing number of go public companies listed on theIndonesia Stock Exchange (IDX). This study uses Audit delayas the dependent, and three other independent variables, namely Auditor Change, company financial difficulty orfinancial distress and KAP Reputation. This research wasconducted on the Indonesia Stock Exchange based on thefinancial statements of real estate and real estate companiesin 2019 - 2022. The negative non-financial impact can be in the form of a bad company image, loss of trust fromstakeholders. Therefore, companies must pay attention to thelength of audit delay or audit report lag. The results showedthat there was a significant effect of Audit Change, Financial Difficulties, Public Accounting Firm on Audit Delay on theIndonesia Stock Exchange based on the reports of real estateand real estate companies in 2019 - 2022, this is evidencedbased on the results of the study.